Opportunities for Change in Small Ruminant Systems in Central Java-Indonesia - Budisatria, I Gede Suparta; Udo, HMJ; Viets, TC; Van der Zijpp, AJ (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2012)
Abstract. This study evaluated sheep fattening and goat breeding innovation scenarios for small ruminant systems in Central Java. In sheep fattening scenario 1, farmers were proposed to fatten 5 male sheep two times a year, in sheep fattening scenario 2, farmers were proposed to fatten sheep in one round of 9 months up to the age of one year. In sheep fattening scenario 3, farmers were proposed to fatten male sheep in two periods, one round with 5 animals as in scenario 1, and another round with 5 animals sold at one year of age for Idul Adha. Goat breeding scenarios were based on a breeding unit with 3 does and involved reductions of kidding intervals from 278 (middle zone) and 273 (uplands) days to 240 and 220 days. The sheep fattening scenarios indicated that if farmers could start specialising in sheep fattening, the technical and economic results could be improved compared to the present sheep production system. Sheep fattening scenario 3 showed the highest net live-weight production in kg and the highest value added. When the opportunity labour costs were included in the calculations, fattening of sheep still produced a positive net return to the farmers. A goat breeding unit with 3 does produced 2.2 and 1.7 times more kids than in the real situation in the middle zone and uplands, respectively. Reducing kidding intervals resulted in an increase of kids sold by 1.2 and 1.3 respectively for kidding intervals 240 and 220 days in the middle zone; while in the uplands this was 1.1 and 1.3 times respectively. The breeding scenario calculations indicated that goat breeding could make a positive contribution to the livelihood of goat farmers, if the management of goats was improved.Keywords:Â sheep fattening, goats breeding, value added, IndonesiaAnimal Production 14(1):37-46, January 2012